The effect of ketamine on eye movement characteristics during free-viewing of natural images in common marmosets - Polyakova, Zlata; Iwase, Masao; Hashimoto, Ryota; Yoshida, Masatoshi (Frontiers in Neuroscience, 2022)
Various eye movement abnormalities and impairments in visual information processing have been reported in patients with schizophrenia. Therefore, dysfunction of saccadic eye movements is a potential biological marker for schizophrenia. In the present study, we used a pharmacological model of schizophrenia symptoms in marmosets and compared the eye movement characteristics of marmosets during free-viewing, using an image set identical to those used for human studies. It contains natural and complex images that were randomly presented for 8 s. As a pharmacological model of schizophrenia symptoms, a subanesthetic dose of ketamine was injected intramuscularly for transient and reversible manipulation. Eye movements were recorded and compared under a ketamine condition and a saline condition as a control. The results showed that ketamine affected eye movement characteristics during free-viewing. Saccades amplitude and scanpath length were significantly reduced in the ketamine condition. In addition, the duration of saccades was longer under the ketamine condition than under the saline condition. A similar tendency was observed for the duration of fixations. The number of saccades and fixations tended to decrease in the ketamine condition. The peak saccades velocity also decreased after ketamine injection whereas there was no difference in the main sequence relationship between saccades amplitude and peak velocity. These results suggest that ketamine affected visual exploration but did not affect the oculomotor aspect of saccades in marmosets, consistent with studies in patients with schizophrenia. Therefore, we conclude that the subanesthetic dose of ketamine is a promising pharmacological model of schizophrenia symptoms in common marmosets and can be used in combination with free-viewing paradigms to establish “translatable markers” for schizophrenia in primates.